The Association between Burning Mouth Syndrome and Level of Thyroid Hormones in Hashimotos Thyroiditis in Public Hospitals in Shiraz, 2016 - Zahra Talattof; Mohammad Hossein Dabbaghmanesh; Yasaman Parvizi; Negin Esnaashari; Azita Azad (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Burning sensation in Hashimoto patient's oral cavity is an unknown prevalent problem. Purpose: This study aimed to evaluate the prevalence and intensity of burning mouth syndrome (BMS) in patients suffering from Hashimoto's thyroiditis in all public hospitals in Shiraz, 2016. Materials and Method: A total of 153 patients with Hashimoto's thyroiditis were selected based on simple random sampling. The initial level of thyroid stimulating hormone (TSH), Anti-TPO (thyroperoxidase), Anti-TG (thyroglobulin), Free T3 (triiodothyronine) and Free T4 (thyroxine) serum as the indices of Hashimoto's thyroiditis was assessed. The BMS intensity was measured according to each patient's verbal or nonverbal expression about the pain experience based on visual analog scale (VAS). Results: Based on the clinical evaluation and interview, only 19out of 153 cases (12%) reported BMS. The mean BMS was 3 based on VAS. Statistically significant association was detected between the level of TSH (p= 0.0001), Anti-TPO (p= 0.035), Anti-TG (p= 0.0001), Free T3 (p= 0.0001), Free T4 (p= 0.0001) indices in patients with BMS. Significant association was also observed between the level of Anti-TPO (p= 0.0001), Anti-TG (p= 0.0001), Free T3 (p= 0.0001) and TSH (p= 0.0001) indices and BMS intensity. However, no significant association was found between the BMS severity and Free T4 (p= 0.056). Conclusion: The level of TSH, Anti-TPO, and Anti-TG, Free T3, and TSH indices of Hashimoto's patients were associated with the presence and severity of BSM. However, Free T4 level was only associated with the presence of BMS and not the intensity.